Anesthesia Management of a Liver Transplant Recipient with Remimazolam - Takashi Kawasaki; Takafumi Oyoshi; Naoyuki Hirata (Case Reports in Anesthesiology)
Background. Intraoperative anesthetic requirements might be altered due to the modulated metabolic function in living donor liver transplant recipients. Remimazolam may provide appropriate anesthesia in patients with cirrhosis. However, the efficacy and safety of remimazolam in liver transplant recipients have not been reported. We present the successful anesthesia management of a liver transplant recipient using remimazolam. Case Presentation. A 54-year-old woman who was diagnosed with Child-Pugh C cirrhosis of unknown etiology was scheduled for living donor liver transplantation. Remimazolam was used for anesthesia management under electroencephalogram monitoring, including bispectral index (BIS) and patient state index (PSI) values. Despite the prolonged surgical time (1,037 min) and massive blood loss (22,500 mL), BIS and PSI values were maintained within acceptable ranges intraoperatively. There was no intraoperative awareness/recall or adverse events associated with remimazolam administered perioperatively. Conclusions. We safely managed general anesthesia for living donor liver transplantation with remimazolam using electroencephalogram monitoring.